Bio-carrier–enhanced aerobic granulation: Effects on the extracellular polymeric substances production and microorganism community. (October 2021) - Lin, Huihua; Sun, Shichang; Lin, Zipeng; Chen, Manting; Fang, Lin; Ma, Rui; Lin, Junhao; Luo, Juan
Abstract: In this study, the strengthening effect of bio-carrier inoculation in the process of aerobic granulation and its influence on the microbial secretion of extracellular polymeric substances (EPS) has been systematically explored, to further understand and perfect the rapid granulation mechanism. Complete granulation was achieved within 15 days, and the granule morphology realized in a reactor inoculated with the bio-carrier (R1) was better than that in the control group (R2), in which complete granulation was not achieved during the entire operation period. However, AGS gradually disintegrated after the 20th day because of the strong shearing force, the crushed AGS enhanced granulation, however did not ensure stability. The average EPS content in R1 20 mg﹒gVSS −1 higher than that in R2, and the protein (PN) content changes around 41.23–82.56 mg﹒gVSS −1 during the granulation process. This indicates that the bio-carrier stimulates microorganisms to secrete more EPS, and PN may have a greater effect on the aggregation of microorganisms. The results showed that the addition of the bio-carrier shortened the AGS granulation time, and increased the EPS content, and the broken AGS played an auxiliary role as the nucleus for floc attachment. Graphical abstract: Image 1 Highlights: The addition of the bio-carrier enables the fully granulated of sludge within 15 d; Protein has a greater effect on the aggregation of microbes than Polysaccharides; Bio-carrier increased the diversity, and uniformity of aerobic granular microbes; The microbes secrete more extracellular polymeric substances, help to aggregate; The crushed aerobic granular enhanced granulation, however did not ensure stability.